2019
DOI: 10.3390/app9142792
|View full text |Cite
|
Sign up to set email alerts
|

The Design and Building of a Hexapod Robot with Biomimetic Legs

Abstract: A hexapod robot with biomimetic legs was built to implement a distributed control system, where a mechanism is proposed to serve as the central pattern generator and a computer to act as the brain-stem, cooperating with the central pattern generator through wireless communication. The proposed mechanism is composed of two modules, i.e., the tripod gait generator and the Theo Jansen Linkage. The tripod gait generator is a device that uses a single motor to generate a tripod gait, while the Theo Jansen Linkage r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…In [Ali et al 2013] the FPGA is used for servo motor control in a six-legged robot platform. Other recently introduced solutions concerning the design and control of a walking robot can be found in [Hwang et al 2019] and [Žák, Rozman and Zbořil 2021].…”
Section: Fig 1 Typical Configurations Of Wheeled Robotsmentioning
confidence: 99%
“…In [Ali et al 2013] the FPGA is used for servo motor control in a six-legged robot platform. Other recently introduced solutions concerning the design and control of a walking robot can be found in [Hwang et al 2019] and [Žák, Rozman and Zbořil 2021].…”
Section: Fig 1 Typical Configurations Of Wheeled Robotsmentioning
confidence: 99%
“…The proposed design outperformed previous works in terms of throughput per area. M. C. Hwang et al [8] reported on "The Design and Building of a Hexapod Robot with Biomimetic Legs". A hexapod robot with biomimetic legs was built to implement a distributed control system, where a mechanism is proposed to serve as the central pattern generator and a computer to act as the brain stem, cooperating with the central pattern generator through wireless communication.…”
Section: Topics Of Selected Papersmentioning
confidence: 99%
“…For flat terrain, rolling robots have the characteristics of fast-moving speed and wide range of motion [1]. Compared with wheeled, tracked, or legged structures [2][3][4], they have smaller volume and higher fault tolerance. When facing rough terrain or large obstacles, jumping robots are obviously the most reasonable choice, which can surmount an obstacle of their own size, or even several times their own size [5].…”
Section: Introductionmentioning
confidence: 99%